∫ 0 1 { x 1 7 2 9 1 − ( 1 − x ) 1 7 2 9 1 } x 6 ( 1 − x ) 6 d x = b a
The equation above holds true for coprime positive integers a and b . Find a + b .
Bonus : Generalize it.
Notation : { ⋅ } denotes the fractional part function .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
exactly the same way i did it!
How did you equate this {f(x)}=({f(x)}+{f(1-x)})/2 in first step ??? You can't equate them as f(x)=-f(1-x) so {f(x)} = 1-{f(1-x)}
Log in to reply
The second term comes from a y = 1 − x substitution, with y then replaced by x ...
Problem Loading...
Note Loading...
Set Loading...
If f is a function such that f ( 1 − x ) = − f ( x ) then, since { u } + { − u } = 1 for all u , we have ∫ 0 1 { f ( x ) } x n ( 1 − x ) n d x = = = 2 1 ∫ 0 1 [ { f ( x ) } + { f ( 1 − x ) } ] x n ( 1 − x ) n d x 2 1 ∫ 0 1 x n ( 1 − x ) n d x = 2 1 B ( n + 1 , n + 1 ) 2 ( 2 n + 1 ) ! ( n ! ) 2 With f ( x ) = x − 1 7 2 9 − ( 1 − x ) − 1 7 2 9 and n = 6 , the integral equals 2 × 1 3 ! ( 6 ! ) 2 = 2 4 0 2 4 1 , and so the answer is 2 4 0 2 5 .